Factors Influencing Purchase Intention to Men’s Apparel Sold Online - Hartanto, Tan Kevin; Agustini, Maria Yosephine Dwi Hayu (Soegijapranata Catholic University, 2025)
Attention to purchase intention on apparel products that has been associated solely with women is now directed to men. The sellers of men's apparel thus need to know the factors influencing intention to purchase men's clothing in order to improve their business. This research aims to understand the influence of fashion awareness, price, and social media advertising on the intention to purchase men's apparel products from e-commerce. The primary data was obtained using a questionnaire distributed in the form of Google forms to men who had bought apparel from e-commerce. The completed 201 questionnaires were analyzed using regression analysis. The results indicate that fashion awareness, price, and social media advertising partially and simultaneously have a positive and significant effect on the intention to purchase men's apparel products sold in e-commerce. They show a moderate contribution of 48.5 percent, which indicate the existence of other factors outside those examined in this research.